ANALISIS BIBLIOMETRIK PENGGUNAAN ANALISIS SURVIVAL MODEL REGRESI COX - Mugiadi, Ridwan P.; Purnomo, Ragil; Nurmalitasari, Fahmi; Mustofa, Rasyid Mei; Wahyudin, Wahyudin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This study aims to conduct a bibliometric analysis of the use of Survival Analysis with the Cox Regression Model in scientific literature. This method has become increasingly relevant in the context of medical, epidemiological, and health science research. Bibliometric analysis was conducted to understand the extent to which these methods are adopted, publication trends over time, as well as identification of collaborations and geographic distribution of research. By collecting and analyzing data from relevant scientific databases, we detailed the number of publications that used Survival Analysis with Cox Regression Models, noted changes in trends over time, and identified the contributions of researchers and institutions. The results of the analysis also include an exploration of the main research topics using this method. The results of the bibliometric research show that there are 5 authors who stand out in publications regarding the survival analysis of the Cox regression model and they have a close relationship. In the title trend analysis, 9 clusters were identified. Keywords that often appear in abstracts and are closely related to